Process method for improving electrolytic tin deposition quality
By using stannous sulfate, sulfuric acid and methylsulfonic acid mixed electrolyte during the tin electrolytic refining process and adding specific additives, the problems of cumbersome operation and long process in the prior art are solved, and efficient and environmentally friendly production of high-purity tin is achieved.
Patent Information
- Application Number
- CN202510035535.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
AI Technical Summary
The existing tin electrolytic refining methods have problems such as cumbersome operation, which may cause environmental pollution or long processes, and it is difficult to meet the needs of industrial production.
The acidic electrolyte containing tin is prepared by mixing stannous sulfate, sulfuric acid and methylsulfonic acid, and 2-naphthol, gelatin and calcium lignin sulfonate as additives to obtain high-purity tin product through electrolytic deposition.
It significantly improves the cathode polarization value and grain refinement degree, improves the uniformity and quality of the deposition products, is simple to operate, short time, low cost, and is environmentally friendly and non-toxic.
Smart Images

Figure CN119824482A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of tin electrolytic refining, and more specifically, relates to a process method for improving the quality of electrolytic tin deposition. Background Art
[0002] Tin metal has shown wide application value in many industrial fields due to its excellent conductivity, low electrochemical migration, considerable weldability, good corrosion resistance and relatively low material cost. As a strategic reserve resource in the field of high-tech, it is widely used in semiconductor device materials in the electronics industry, the manufacture of alloy parts in aerospace, and the coating material of solar photovoltaic cells in the field of new energy. With its wide and in-depth application scenarios, tin metal has become one of the most popular important materials in the world.
[0003] In the early days of tin metal smelting, traditional pyrometallurgical technology was the main method of producing tin, using blast furnaces, reverberatory furnaces and other equipment for smelting. Although this method has a high impurity removal efficiency, it is costly, produces a large amount of by-products and waste (i.e., "three wastes"), has low production efficiency and a complicated and cumbersome operation process. At present, the industry relies more on electrochemical deposition to produce high-purity tin metal through electrolytic refining. This process involves using electrochemical principles in a specific electrolyte solution to cause the crude tin material on the anode to react, and then depositing high-purity tin layer by layer on the cathode surface. This method can ensure that the produced tin is of high purity and meet more stringent application requirements.
[0004] The Chinese patent application number is CN201110238630.9, and the patent document with the publication date of December 28, 2011 discloses a method for preparing high-purity tin, which comprises the following steps: (1) preparing tin tetrachloride, reacting 500g of granular metallic tin with chlorine gas washed with distilled water and concentrated sulfuric acid to generate tin tetrachloride; (2) fractionating and purifying tin tetrachloride, (3) synthesizing tin hydroxide, and (4) reducing to obtain high-purity tin, transferring the tin hydroxide obtained in step (3) to a quartz boat, placing the quartz boat in a quartz tube, and reducing with hydrogen to obtain high-purity tin. The invention first prepares tin tetrachloride, then purifies it by fractionation technology, and then synthesizes tin hydroxide, and finally reduces it with hydrogen to obtain high-purity tin, but the operation is cumbersome and involves chemical processes such as chlorination, which may have a significant impact on the ecological environment and fail to fully meet the environmental protection requirements advocated by the current green metallurgy concept.
[0005] The Chinese patent application number is: CN202110205951.2, and the patent document with the publication date of June 11, 2021 discloses a method for preparing high-purity tin, which comprises the following steps: preparation for the first electrolysis: first inject sulfuric acid solution into the electrolytic cell, the solvent of the sulfuric acid solution is ultrapure water, and then place the crude tin plate in the sulfuric acid solution in the electrolytic cell as an anode, and then put the conductive plate into the diaphragm bag. After loading, the top of the conductive plate is higher than the top bag opening of the diaphragm bag, and then place the diaphragm bag in the sulfuric acid solution in the electrolytic cell, and then fill the diaphragm bag with sulfuric acid solution. At this time, the conductive plate is the cathode; the first electrolysis: first connect the crude tin plate and the conductive plate to the positive and negative poles of the DC power supply respectively, and then turn on the power supply and adjust the current density for electrolysis until the tin concentration in the electrolytic cell reaches 50-80g / L and then stop the electrolysis. At this time, the liquid in the electrolytic cell is a tin solution. The method first injects a sulfuric acid solution, uses crude tin as an anode and a conductive plate as a cathode to perform a primary electrolysis, takes out the tin solution obtained by the primary electrolysis, adds a polarizer, a chelating agent A, an antioxidant, and a filter, mixes evenly to obtain an electrolyte, and performs a secondary electrolysis to obtain high-purity tin. Although the operation is simple and the cost is low, the entire process requires secondary electrolysis, which is time-consuming and not conducive to industrial production. Summary of the invention
[0006] 1. Problems to be solved
[0007] In view of the problems of the existing tin electrolytic refining methods, such as complicated operation, possible environmental pollution or long process, the present invention provides a process method for improving the quality of electrolytic tin deposition, which can significantly increase the cathode polarization value, significantly refine the grains, improve the uniformity of the deposition product, ensure the deposition quality of the electrolytic tin, and has the advantages of simple operation, short time consumption, low cost and green environmental protection.
[0008] 2. Technical solution
[0009] To solve the above problems, the present invention adopts the following technical solutions.
[0010] A process for improving the quality of electrolytic tin deposition comprises the following steps:
[0011] (1) mixing stannous sulfate, sulfuric acid and methanesulfonic acid to obtain a tin-containing acidic electrolyte;
[0012] (2) adding a set amount of 2-naphthol, gelatin, and calcium lignin sulfonate as an additive to the electrolyte obtained in step (1) and performing a constant volume treatment;
[0013] (3) Using a crude tin plate as an anode and a pure titanium plate as a cathode, electrolytic deposition is carried out in a constant volume electrolyte to obtain a refined tin product.
[0014] As a further improvement of the technical solution, in the tin-containing electrolyte of step (1), the concentration of stannous sulfate is 10-30 g / L, the concentration of sulfuric acid is 50-80 g / L, and the concentration of methanesulfonic acid is 35-50 g / L.
[0015] As a further improvement of the technical solution, in the electrolyte after the constant volume treatment in step (2), the concentration of 2-naphthol is 0.5-2 g / L, the concentration of gelatin is 0.7-1.5 g / L, and the concentration of calcium lignin sulfonate is 0.3-1 g / L.
[0016] As a further improvement of the technical solution, in step (3), the anode plate is wrapped with polyester filter cloth.
[0017] As a further improvement of the technical solution, in step (3), the cathode plate is polished to remove oxides on its surface using 400-mesh, 1000-mesh and 2000-mesh sandpapers respectively.
[0018] As a further improvement of the technical solution, in step (3), the side and back of the cathode plate are coated with non-conductive sealing silicone.
[0019] As a further improvement of the technical solution, in step (3), the reaction time of the electrolytic deposition process is 8-24 hours.
[0020] As a further improvement of the technical solution, in step (3), the reaction temperature of the electrolytic deposition process is 20-40°C.
[0021] As a further improvement of the technical solution, in step (3), the cell voltage of the electrolytic deposition process is 0.2-0.4V.
[0022] As a further improvement of the technical solution, in step (3), the cathode current density of the electrolytic deposition process is 60-80A / m 2 .
[0023] 3. Beneficial effects
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The present invention provides a process for improving the quality of electrolytic tin deposition. The dissociated gelatin carries positively charged colloid roots, which migrate toward the cathode during electrolysis and are tightly adsorbed on its surface active sites, thereby enhancing the polarization effect of the cathode surface. At the same time, as surfactant additives with negative electrical properties, 2-naphthol and calcium lignin sulfonate promote electrophoresis to move toward the anode, greatly improving the polarization degree of the anode surface, so that the crude tin on the anode can be dissolved more evenly. Through the mutual compounding and coordination of gelatin, 2-naphthol and calcium lignin sulfonate, the quality of the electrolysis product is significantly improved, the grains are obviously refined, and the flatness and glossiness of the product are effectively improved.
[0026] (2) The present invention provides a process for improving the quality of electrolytic tin deposition, which uses a sulfate system instead of the traditional alkaline stannate and fluoroboric acid system for electrolytic tin deposition, and has the advantages of simple operation, low cost, short time consumption, high economic benefit, good impurity tolerance, etc.
[0027] (3) The present invention provides a process for improving the quality of electrolytic tin deposition, wherein the components of the tin-containing electrolyte are environmentally friendly, safe and non-toxic, easily degraded in the environment, and the electrolyte has high stability;
[0028] (4) The present invention provides a process for improving the quality of electrolytic tin deposition, which is simple to operate, low in cost, low in energy consumption, high in current efficiency and environmentally friendly. It optimizes the kinetics of the electroplating process of tin ions on the cathode and deposits flat and dense high-purity tin metal on the titanium electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is a SEM image of the cathode deposition product of Example 1, wherein: Figure 1 (a) is a microscopic morphology image magnified 100 times. Figure 1 (b) is a microscopic morphology image magnified 1000 times;
[0030] Figure 2 This is a SEM image of the cathode deposition product of Example 2, wherein: Figure 2 (a) is a microscopic morphology image magnified 100 times. Figure 1 (b) is a microscopic morphology image magnified 1000 times;
[0031] Figure 3 This is a SEM image of the cathode deposition product of Example 3, wherein: Figure 3 (a) is a microscopic morphology image magnified 100 times. Figure 1 (b) is a microscopic morphology image magnified 1000 times;
[0032] Figure 4 This is a SEM image of the cathode deposition product of Example 4, wherein: Figure 4(a) is a microscopic morphology image magnified 100 times. Figure 1 (b) is a microscopic morphology image magnified 1000 times;
[0033] Figure 5 This is the SEM image of the cathode deposition product of Comparative Example 1, where: Figure 5 (a) is a microscopic morphology image magnified 100 times. Figure 5 (b) is a microscopic morphology image magnified 1000 times;
[0034] Figure 6 This is the SEM image of the cathode deposition product of Comparative Example 2, where: Figure 6 (a) is a microscopic morphology image magnified 100 times. Figure 6 (b) is a microscopic morphology image magnified 1000 times;
[0035] Figure 7 This is the SEM image of the cathode deposition product of Comparative Example 3, where: Figure 7 (a) is a microscopic morphology image magnified 100 times. Figure 7 (b) is a microscopic morphology image magnified 1000 times;
[0036] Figure 8 This is a SEM image of the cathode deposition product of Comparative Example 4, wherein: Figure 8 (a) is a microscopic morphology image magnified 100 times. Figure 8 (b) is a microscopic morphology image magnified 1000 times;
[0037] Fig. 9 is the XRD pattern of the electrolytic tin deposition product of Examples 1-4;
[0038] Fig.10 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION
[0039] Exemplary embodiments of the present invention are described in detail below. Although these exemplary embodiments are described in sufficient detail to enable those skilled in the art to implement the present invention, it should be understood that other embodiments may be implemented and various changes may be made to the present invention without departing from the spirit and scope of the present invention. The more detailed description of the embodiments of the present invention below is not intended to limit the scope of the claimed invention, but is merely for illustration and does not limit the description of the features and characteristics of the present invention, in order to propose the best mode for performing the present invention, and is sufficient to enable those skilled in the art to implement the present invention. Therefore, the scope of the present invention is limited only by the appended claims.
[0040] At present, the industry mostly relies on electrochemical deposition to produce high-purity tin metal by electrolytic refining. This process involves using electrochemical principles in a specific electrolyte solution to cause the crude tin material on the anode to react, and then depositing high-purity tin layer by layer on the cathode surface. However, in actual production, the existing tin electrolytic refining method often has the problem of cumbersome operation, possible environmental pollution, or long process. In view of these problems, the present invention provides a process method for improving the quality of electrolytic tin deposition, which solves the above problems while ensuring the deposition quality of electrolytic tin.
[0041] like Fig.10 As shown, the process of the present invention mainly comprises the following steps:
[0042] (1) Stannous sulfate, sulfuric acid and methanesulfonic acid are mixed to obtain a tin-containing acidic electrolyte.
[0043] In this step, the concentration of stannous sulfate is 10-30 g / L, the concentration of sulfuric acid is 50-80 g / L, and the concentration of methanesulfonic acid is 35-50 g / L.
[0044] (2) Predetermined amounts of 2-naphthol, gelatin, and calcium lignin sulfonate are compounded and added as additives to the electrolyte obtained in step (1) and the mixture is fixed to volume.
[0045] In this step, in the electrolyte after constant volume treatment, the concentration of 2-naphthol is 0.5-2g / L, the concentration of gelatin is 0.7-1.5g / L, and the concentration of calcium lignin sulfonate is 0.3-1g / L. The molecular formula of 2-naphthol is C 10 H8O, as a basic brightener and solubilizer, is used to increase the adhesion of cathode deposits. In addition, 2-naphthol makes the anode mud loose to reduce the interference of the anode mud on the electrolysis process and improve the electrolysis efficiency. The molecular formula of gelatin is C 102 H 151 O 39 N 31 As a colloidal medium, it can significantly increase the viscosity of the electrolyte, further enhance the polarization of the cathode, and thus refine the grains. The molecular formula of calcium lignin sulfonate is C 20 H 24 CaO 10 S2, as a leveling agent, is used to improve the crystallization quality of cathode products, refine grains, and reduce porosity. In addition, it can form complexes with some impurity ions in the electrolyte to improve the purity of electrolytic products.
[0046] (3) Using a crude tin plate as an anode and a pure titanium plate as a cathode, electrolytic deposition is carried out in a constant volume electrolyte to obtain a refined tin product.
[0047] In this step, the anode plate is wrapped with polyester filter cloth to collect the anode mud produced during the electrolysis process. The cathode plate is polished with 400 mesh, 1000 mesh and 2000 mesh sandpaper to remove the oxide on its surface, and the side and back are coated with non-conductive sealing silicone to reduce the edge effect and the generation of dendrites during the electrolysis process.
[0048] The reaction time of the electrolytic deposition process is 8-24h, the reaction temperature is 20-40℃, the cell voltage is 0.2-0.4V, and the cathode current density is 60-80A / m 2 .
[0049] This method uses a sulfate system instead of the traditional alkaline stannate and fluoroboric acid system for electrolytic tin deposition, which has the advantages of simple operation, low cost, short time, high economic benefit, good impurity tolerance, etc. At the same time, the components of the tin-containing electrolyte are environmentally friendly, safe and non-toxic, easy to degrade in the environment, and the electrolyte has high stability. It has high current efficiency and is green and environmentally friendly, optimizes the kinetics of the electrodeposition process of tin ions on the cathode, and deposits flat and dense high-purity tin metal on the titanium plate.
[0050] The dissociated gelatin will carry positively charged colloid roots, which will migrate toward the cathode during electrolysis and be tightly adsorbed on its surface active sites, thereby enhancing the polarization effect of the cathode surface. At the same time, as surfactant additives with negative electrical properties, 2-naphthol and calcium lignin sulfonate promote the movement of electrophoresis toward the anode, greatly improving the polarization degree of the anode surface and enabling the crude tin on the anode to be dissolved more evenly. Through the mutual coordination of gelatin, 2-naphthol and calcium lignin sulfonate, the quality of the electrolysis product is significantly improved, the grain refinement is obvious, and the flatness and glossiness of the product are effectively improved.
[0051] The technical effect of the present method is further demonstrated by specific examples and comparative examples.
[0052] Example 1
[0053] A process for improving the quality of electrolytic tin deposition comprises the following steps:
[0054] (1) Prepare a tin-containing acid electrolyte, dilute sulfuric acid, heat and boil, then add 2-naphthol, heat and dissolve gelatin and calcium lignin sulfonate in water, mix with stannous sulfate and methanesulfonic acid and shake well. The concentration of 2-naphthol is 1.5 g / L, the concentration of gelatin is 1 g / L, the concentration of calcium lignin sulfonate is 0.5 g / L, the concentration of stannous sulfate is 15 g / L, the concentration of sulfuric acid is 60 g / L, and the concentration of methanesulfonic acid is 35 g / L. The above components are fixed to a volume of 150 mL of electrolyte.
[0055] (2) The electrolyte was placed in an electrolytic cell, with a crude tin plate as the anode and a pure titanium plate as the cathode. The electrolysis temperature was controlled at 25°C, and the cathode current density was set at 60A / m 2 The cathode product tin metal was obtained after electrolysis for 12 hours. The test results in Table 1 show that after the three additives were coordinated, the cell voltage was 0.271V, the energy consumption was 0.133KWh / kg, and the current efficiency was 92.3%. Figure 1 It can be seen that the surface of the deposited product is highly flat, there are no obvious dendritic tin grains, the grains are small and the density is high. XRD ( Fig. 9 ) The results show that no SnO2 impurity peaks appear in the phase detection, and the diffraction peak intensities of the (101) and (211) crystal planes are significantly higher than those of other crystal planes, indicating that preferential growth occurs on the (101) and (211) crystal planes.
[0056] Example 2
[0057] A process for improving the quality of electrolytic tin deposition includes the following steps.
[0058] (1) Prepare a tin-containing acid electrolyte, dilute sulfuric acid, heat and boil, then add 2-naphthol, heat and dissolve gelatin and calcium lignin sulfonate in water, mix with stannous sulfate and methanesulfonic acid and shake well. The concentration of 2-naphthol is 1.2 g / L, the concentration of gelatin is 1.1 g / L, the concentration of calcium lignin sulfonate is 0.7 g / L, the concentration of stannous sulfate is 15 g / L, the concentration of sulfuric acid is 60 g / L, and the concentration of methanesulfonic acid is 35 g / L. The above components are fixed to a volume of 150 mL of electrolyte.
[0059] (2) The electrolyte was placed in an electrolytic cell, with a crude tin plate as the anode and a pure titanium plate as the cathode. The electrolysis temperature was controlled at 25°C and the cathode current density was set at 60 A / m 2 The cathode product tin metal was obtained after electrolysis for 12 hours. The test results in Table 1 show that after the three additives were coordinated, the cell voltage was 0.315V, the energy consumption was 0.155KWh / kg, and the current efficiency was 91.7%. Figure 2 It can be seen from the XRD results that the surface of the deposited product is flat and dense, with no obvious protrusion of tin grains and no gaps between grains. Fig. 9 ) The results show that no SnO2 impurity peaks appear in the phase detection, and the diffraction peak intensities of the (101) and (211) crystal planes are significantly higher than those of other crystal planes, indicating that preferential growth occurs on the (101) and (211) crystal planes.
[0060] Example 3
[0061] A process for improving the quality of electrolytic tin deposition comprises the following steps:
[0062] (1) Prepare a tin-containing acid electrolyte, dilute sulfuric acid, heat and boil, then add 2-naphthol, heat and dissolve gelatin and calcium lignin sulfonate in water, mix with stannous sulfate and methanesulfonic acid and shake well. The concentration of 2-naphthol is 1.2 g / L, the concentration of gelatin is 0.8 g / L, the concentration of calcium lignin sulfonate is 1 g / L, the concentration of stannous sulfate is 15 g / L, the concentration of sulfuric acid is 60 g / L, and the concentration of methanesulfonic acid is 35 g / L. The above components are fixed to a volume of 150 mL of electrolyte.
[0063] (2) The electrolyte was placed in an electrolytic cell, with a crude tin plate as the anode and a pure titanium plate as the cathode. The electrolysis temperature was controlled at 25°C and the cathode current density was set at 60 A / m 2 The cathode product tin metal was obtained after electrolysis for 12 hours. The test results in Table 1 show that after the three additives were coordinated, the cell voltage was 0.294V, the energy consumption was 0.141KWh / kg, and the current efficiency was 94.2%. Figure 2 It can be seen that the surface of the deposited product is highly flat, the tin grains are small and have no gaps, and there are no obvious tin grains protruding from the surface. XRD ( Fig. 9 ) The results show that no SnO2 impurity peaks appear in the phase detection, and the diffraction peak intensities of the (101) and (211) crystal planes are significantly higher than those of other crystal planes, indicating that preferential growth occurs on the (101) and (211) crystal planes.
[0064] Example 4
[0065] A process for improving the quality of electrolytic tin deposition comprises the following steps:
[0066] (1) Prepare a tin-containing acid electrolyte, dilute sulfuric acid, heat and boil, then add 2-naphthol, heat and dissolve gelatin and calcium lignin sulfonate in water, mix with stannous sulfate and methanesulfonic acid and shake well. The concentration of 2-naphthol is 1.3 g / L, the concentration of gelatin is 0.7 g / L, the concentration of calcium lignin sulfonate is 1 g / L, the concentration of stannous sulfate is 30 g / L, the concentration of sulfuric acid is 60 g / L, and the concentration of methanesulfonic acid is 35 g / L. The above components are fixed to a volume of 150 mL of electrolyte.
[0067] (2) The electrolyte was placed in an electrolytic cell, with a crude tin plate as the anode and a pure titanium plate as the cathode. The electrolysis temperature was controlled at 25°C and the cathode current density was set at 60 A / m 2 The cathode product tin metal was obtained after electrolysis for 12 hours. The test results in Table 1 show that after the three additives were coordinated, the cell voltage was 0.297V, the energy consumption was 0.147KWh / kg, and the current efficiency was 91.4%. Figure 4 It can be seen that the surface of the deposited product is dense and flat, there are no obvious protruding tin grains on the surface, the tin grains are small and there is no obvious gap. XRD ( Fig. 9) The results show that no SnO2 impurity peaks appear in the phase detection, and the diffraction peak intensities of the (101) and (211) crystal planes are significantly higher than those of other crystal planes, indicating that preferential growth occurs on the (101) and (211) crystal planes.
[0068] Comparative Example 1
[0069] The method comprises the following steps:
[0070] (1) Prepare a tin-containing acidic electrolyte by diluting sulfuric acid, heating it to boil, and then mixing it with stannous sulfate and methanesulfonic acid and shaking it evenly. The concentration of stannous sulfate is 30 g / L, the concentration of sulfuric acid is 60 g / L, and the concentration of methanesulfonic acid is 35 g / L. The above components are fixed to a volume of 150 mL of electrolyte.
[0071] (2) The electrolyte was placed in an electrolytic cell, with a crude tin plate as the anode and a pure titanium plate as the cathode. The electrolysis temperature was controlled at 25°C and the cathode current density was set at 60 A / m 2 The cathode product tin metal was obtained after electrolysis for 12 hours. Comparative Examples 1 to 4, when no additive was added during the tin electrolysis process, the test results in Table 1 showed that the cell voltage was 0.512V, the energy consumption was 0.295KWh / kg, and the current efficiency was 78.4%. The cell voltage and energy consumption were significantly increased, and the current efficiency was reduced. Figure 5 It can be seen that a large amount of deposited products fall off, the bonding force between the deposited layer and the plate is poor, and the surface presents a loose and non-dense morphology. It can be seen that the economic benefits and product quality of Comparative Example 1 are lower than those of Examples 1-4.
[0072] Comparative Example 2
[0073] The method comprises the following steps:
[0074] (1) Prepare a tin-containing acid electrolyte, dilute sulfuric acid, heat and boil, dissolve calcium lignin sulfonate in water, mix with stannous sulfate and methanesulfonic acid and shake well, wherein the concentration of calcium lignin sulfonate is 1.5 g / L, the concentration of stannous sulfate is 30 g / L, the concentration of sulfuric acid is 60 g / L, and the concentration of methanesulfonic acid is 35 g / L, and the above components are fixed to a volume of 150 mL of electrolyte.
[0075] (2) The electrolyte was placed in an electrolytic cell, with a crude tin plate as the anode and a pure titanium plate as the cathode. The electrolysis temperature was controlled at 25°C and the cathode current density was set at 60 A / m 2 The cathode product tin metal was obtained after electrolysis for 12 hours. Comparative Examples 1 to 4, when calcium lignin sulfonate was added as an additive during the tin electrolysis process, the test results in Table 1 showed that the cell voltage was 0.487V, the energy consumption was 0.271KWh / kg, and the current efficiency was 81.3%. Figure 6It can be seen that the flatness of the deposited product is low, and the tin grains grow in a peak shape. It can be seen that the energy consumption and cell voltage of Comparative Example 2 are higher than those of Examples 1-4, while the current efficiency and the quality of the deposited product are lower than those of Examples 1-4.
[0076] Comparative Example 3
[0077] The method comprises the following steps:
[0078] (1) Prepare a tin-containing acidic electrolyte by diluting sulfuric acid, heating it to boil, adding 2-naphthol, mixing it with stannous sulfate and methanesulfonic acid and shaking it evenly. The concentration of 2-naphthol is 2 g / L, the concentration of stannous sulfate is 30 g / L, the concentration of sulfuric acid is 60 g / L, and the concentration of methanesulfonic acid is 35 g / L. The above components are fixed to a volume of 150 mL of electrolyte.
[0079] (2) The electrolyte was placed in an electrolytic cell, with a crude tin plate as the anode and a pure titanium plate as the cathode. The electrolysis temperature was controlled at 25°C and the cathode current density was set at 60 A / m 2 The cathode product tin metal was obtained after electrolysis for 12 hours. Comparative Examples 1 to 4, when 2-naphthol was added as a single additive during the tin electrolysis process, the test results in Table 1 showed that the cell voltage was 0.479 V, the energy consumption was 0.259 KWh / kg, and the current efficiency was 83.5%. Figure 7 It can be seen that the deposited product is in the shape of sponge tin, with a loose and porous surface and more pores. It can be seen that the energy consumption and cell voltage of Comparative Example 3 are higher than those of Examples 1 to 4, while the current efficiency and the quality of the deposited product are lower than those of Examples 1 to 4.
[0080] Comparative Example 4
[0081] The method comprises the following steps:
[0082] (1) A tin-containing acid electrolyte is prepared by diluting sulfuric acid, heating it to boil, and then adding 2-naphthol. Calcium lignin sulfonate is dissolved in water and then mixed with stannous sulfate and methanesulfonic acid and shaken well. The concentration of 2-naphthol is 2 g / L, the concentration of stannous sulfate is 30 g / L, the concentration of sulfuric acid is 60 g / L, and the concentration of methanesulfonic acid is 35 g / L. The above components are fixed to a volume of 150 mL of electrolyte.
[0083] (2) The electrolyte was placed in an electrolytic cell, with a crude tin plate as the anode and a pure titanium plate as the cathode. The electrolysis temperature was controlled at 25°C and the cathode current density was set at 60 A / m 2 The cathode product tin metal was obtained after electrolysis for 12 hours. Comparative Examples 1 to 4, when 2-naphthol and calcium lignin sulfonate were added as additives during the tin electrolysis process, the test results in Table 1 showed that the cell voltage was 0.432V, the energy consumption was 0.229KWh / kg, and the current efficiency was 85.2%. Figure 8It can be seen that there are obvious floccules on the surface of the deposited product, the surface is uneven, and there are many pores. Therefore, it can be seen that the economic benefits and the quality of the deposited product of Comparative Example 4 are lower than those of Examples 1-4.
[0084] The examples described in the present invention are merely descriptions of the preferred implementation modes of the present invention, and are not intended to limit the concept and scope of the present invention. Without departing from the design concept of the present invention, various modifications and improvements made to the technical solutions of the present invention by engineers and technicians in this field should all fall within the protection scope of the present invention.
Claims
1. A process for improving the quality of electrolytic tin deposition, characterized in that: The following steps are involved: (1) mixing stannous sulfate, sulfuric acid and methanesulfonic acid to obtain a tin-containing acidic electrolyte; (2) adding a set amount of 2-naphthol, gelatin, and calcium lignin sulfonate as an additive to the electrolyte obtained in step (1) and performing a constant volume treatment; (3) Using a crude tin plate as an anode and a pure titanium plate as a cathode, electrolytic deposition is carried out in a constant volume electrolyte to obtain a refined tin product.
2. A process for improving the quality of electrolytic tin deposition according to claim 1, characterized in that: In the tin-containing electrolyte of step (1), the concentration of stannous sulfate is 10-30 g / L, the concentration of sulfuric acid is 50-80 g / L, and the concentration of methanesulfonic acid is 35-50 g / L.
3. The process for improving the quality of electrolytic tin deposition according to claim 1, characterized in that: In the electrolyte after the constant volume treatment in step (2), the concentration of 2-naphthol is 0.5-2 g / L, the concentration of gelatin is 0.7-1.5 g / L, and the concentration of calcium lignin sulfonate is 0.3-1 g / L.
4. A process for improving the quality of electrolytic tin deposition according to claim 1, characterized in that: In the step (3), the anode plate is wrapped with polyester filter cloth.
5. A process for improving the quality of electrolytic tin deposition according to claim 4, characterized in that: In the step (3), the cathode plate is polished to remove oxides on its surface using sandpapers of 400 mesh, 1000 mesh and 2000 mesh respectively.
6. A process for improving the quality of electrolytic tin deposition according to claim 5, characterized in that: In the step (3), the side and back of the cathode plate are coated with non-conductive sealing silicone.
7. A process for improving the quality of electrolytic tin deposition according to claim 1, characterized in that: In the step (3), the reaction time of the electrolytic deposition process is 8-24 hours.
8. A process for improving the quality of electrolytic tin deposition according to claim 7, characterized in that: In the step (3), the reaction temperature of the electrolytic deposition process is 20-40°C.
9. A process for improving the quality of electrolytic tin deposition according to claim 8, characterized in that: In the step (3), the cell voltage during the electrolytic deposition process is 0.2-0.4V.
10. A process for improving the quality of electrolytic tin deposition according to claim 9, characterized in that: In step (3), the cathode current density of the electrolytic deposition process is 60-80A / m 2 .
Citation Information
Patent Citations
A method for preparing high-purity tin
CN102296189A
Preparation method of high-purity tin
CN112941565A